Optimising the use of plastic protective covers in field grown melon on a farm scale - Paolo Benincasa; Andrea Massoli; Livia Polegri; Luciano Concezzi; Andrea Onofri; Francesco Tei (Italian Journal of Agronomy)
This in-farm research study was aimed at evaluating new strategies in the use of plastic protective covers in field grown melon in order to expand the production period and reduce costs. Four experiments were set up in 2010 and repeated in 2011 in Central Italy, in an inland region with a temperate climate. We evaluated: i) the use of high tunnels for two growing cycles per year, i.e. for very early and very late production (target transplanting in late winter and mid-summer, respectively), for either one year or two consecutive years, and the use of grafted plants in the second year as an alternative to normal plants to prevent soil born diseases; ii) the use of ethylene-vinyl-acetate film low tunnels alone or combined with non-woven floating row covers for transplanting in early spring; iii) the use of non-woven low tunnels for transplanting in mid-spring; iv) the use of biodegradable and conventional polyethylene ground mulch films, both in the presence of nonwoven low tunnels. As far as the non-woven cover is concerned, we adopted the strategy of removing later with respect to usual practices, i.e. ten days after the onset of first pistillate flowers. This was based on the evidence that covers hamper honeybee circulation, which may be exploited on a farm-scale to delay pollination until an adequate number of pistillate flowers set, in order to shorten scaled fruit ripening and harvest. Our results demonstrate that high tunnels may be used for at least four consecutive melon growing cycles (early and late productions for two years) with good off-season yields and no appreciable drawbacks in terms of disease scale-up, irrespective of the use of normal or grafted plants. The non-woven low tunnel was effective in hampering honeybee circulation and its delayed removal allowed the harvest period to be halved, a more uniform fruit size to be obtained, and labour productivity of harvest to be increased. This had positive implications on the management of irrigation and chemical disease control close to the harvest period, and on the management of harvest and post-harvest operation schedules, including fruit processing, packaging and delivery to markets. In the presence of a non-woven low tunnel, there was no substantial difference in the biodegradable mulch compared to other mulches in terms of effects on harvest dates, yield and weed control, so that its use can be cost-effective and convenient provided that costs are not higher than those for traditional polyethylene films and their usage/disposal.